ANALISIS PENGARUH CORPORATE SOCIAL RESPONSIBILITY (CSR) TERHADAP KEPUASAN MASYARAKAT PADA PT. KIRANA MUSI PERSADA - Oemar, Usailan; -, Zulpaidah (Universitas muhammadiyah palembang, 2016)
Corporate social responsibility (CSR) put the company as the agent of change which is not only has the orientation of maximum profit, but also bring social and moral responsibilities to the whole stakeholders, including the people who live around the company. This research aims to analyze the influence of CSR to the satisfaction of society in PT. Kirana Musi Persada Sekayu. The two variables used are CSR itself and society satisfaction which is developed in to several indicators. The result of this research shows that there is a significant influence of CSR to the society satisfaction of people living around PT. Kirana Musi Persada Sekayu.